Library Electronic services in Ahmed Al-Farsi Library: a simulated approach - Dsilva, Suchita Noel; Waydande, Prof (Dr) Hindurao (IJRDO- Journal of Educational Research, 2017)
Academic libraries have important factors in the process of learning among other factors ofeducation and research. Due to the new electronics technology development and new electronicsstorage media for storage and dissemination of information, Libraries are reengineeringits services; we speak about electronic references, full text data access, Web resources, that areintegral part of education in the electronic environment. E-services can be used byboth consumersand businesses, and can be accessed via a wide range of information appliances (Hoffman, 2003,p.53). This paper focuses on the challenges that e-services are posing and will pose for researchpurpose. The study has focused on the issues thatUniversity of Bahrain (UOB), College of HealthScience (CHS) library has had to deal with as a result of e-services adoption as well as the futurechallenges that e-services provide for CHS, Ahmed Al-Farsi Library (AAFL). The study is basedon a number of conversations with UOB library management & staff and information providedon the Web page. The librarians also have to adapt to this new development for e-delivery andstorage and dissemination of information, to form and to inform about the e-resources forlearning. We have to develop added value services to the role of library as a key factor inlearning.